2007
DOI: 10.1111/j.1755-0238.2007.tb00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of postharvest water stress on lipoxygenase and alcohol dehydrogenase activities, and on the composition of some volatile compounds of Gewürztraminer grapes dehydrated under controlled and uncontrolled thermohygrometric conditions

Abstract: Gewürztraminer grapes with a sugar content of around 212 g/L (21.7°Brix) were dried at 17°C, 40% relative humidity and 1.5 m/sec air flow in a 300 L thermo-conditioned tunnel. Control grapes were dried traditionally in a window ventilated room, under uncontrolled environmental conditions varying with outside climate. Tunnel-dried grapes reached the desired sugar concentration (305 g/L, 29.5°Brix) in 17 days, loosing 36% of their weight. Control grapes lost only 22% of their weight and grey mould developed in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
0
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 24 publications
7
76
0
3
Order By: Relevance
“…Costantini et al (2006) identified the second significant step of metabolic change around this value, with a significant increase in alcohol dehydrogenase activity in Malvasia grape, and this was later confirmed by Wright et al (2009), who observed a change in inflection point in fluorescence (Fo) and in the fructose/glucose ratio at 20-25% of mass loss in table grapes. Grape cell stress through water loss does not only depend on the amount of mass transfer (water), and other factors, such as continuous change in the surrounding vapour pressure, could accelerate the rate of stress (Chkaiban et al, 2007), and the rate of water loss is affected by environmental parameters and varietal characteristics . Malic acid decreased significantly at 10°C, probably due to the shift from harvest temperature down to 10°C (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Costantini et al (2006) identified the second significant step of metabolic change around this value, with a significant increase in alcohol dehydrogenase activity in Malvasia grape, and this was later confirmed by Wright et al (2009), who observed a change in inflection point in fluorescence (Fo) and in the fructose/glucose ratio at 20-25% of mass loss in table grapes. Grape cell stress through water loss does not only depend on the amount of mass transfer (water), and other factors, such as continuous change in the surrounding vapour pressure, could accelerate the rate of stress (Chkaiban et al, 2007), and the rate of water loss is affected by environmental parameters and varietal characteristics . Malic acid decreased significantly at 10°C, probably due to the shift from harvest temperature down to 10°C (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Critical levels of mass loss (weight loss) for these changes have been identified at 10% and 20%, respectively. Chkaiban et al (2007) have, in addition, demonstrated that the stability of dehydration conditions are very important in order to have a ''regular" water stress process in terms of the metabolic changes described above; indeed, if grape berry undergoes continuous change in temperature and relative humidity during dehydration the stress metabolism is accelerated. Wright, DeLong, Lada, and Prange (2009) have shown that the level of mass loss greatly affects fluorescence emission and the critical level is around 20% of mass loss, confirming what was observed by Bellincontro et al (2009) in Cesanese grape using destructive analyses as well as non-destructive techniques.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additional class a transcripts were related to the oxidative burst that occurs at veraison (Pilati et al, 2007). Transcripts in the response-to-stimulus category were found in both classes a and b, including those involved in ethylene (class a) and gibberellin (class b) signaling, whereas several transcripts encoding transcription factors were found in classes b and c. Class c (withering-specific) transcripts included those involved in cell wall metabolism, stress responses, aerobic fermentation, volatile compound synthesis, and cell death, as suggested by previous genomic studies (Zamboni et al, 2008;Rizzini et al, 2009) and physiological investigations (Bellincontro et al, 2004;Costantini et al, 2006;Chkaiban et al, 2007).…”
Section: Data Set Explorationmentioning
confidence: 88%
“…Proteins involved in primary/cellular metabolic processes, sugar catabolism, cellular component organization, and biogenesis were more likely to group in class b, reflecting the activation of glycolysis and gluconeogenesis during ripening (Sarry et al, 2004;Negri et al, 2008). Proteins involved in the switch to aerobic fermentation during ripening (Sarry et al, 2004) and withering Costantini et al, 2006;Chkaiban et al, 2007) were found between classes b and c along with those involved in the production of flavonoids (Coombe and McCarthy, 2000).…”
Section: Data Set Explorationmentioning
confidence: 94%